Influence of aluminium alloy type on dissimilar friction stir lap welding of aluminium to copper - Galvão, I. (2013)
A heat-treatable (AA 6082) and a non-heat treatable (AA 5083) aluminium alloys were friction stir lap welded to copper using the same welding parameters. Macro and microscopic analysis of the welds enabled to detect important differences in welding results, according to the aluminium alloy type. Whereas important internal defects, resulting from ineffective materials mixing, were detected for the AA 5083/copper welds, a relatively uniform material mixing was detected in the AA 6082/copper welds. Micro-hardness testing and XRD analysis also showed important differences in microstructural evolution for both types of welds. TEM and EBSD-based study of the AA 5083/copper welds revealed the formation of submicron-sized microstructures in the stirred aluminium region, for which untypically high hardness values were registered.